2014
DOI: 10.1007/s11356-014-3476-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the genotoxicity of waters impacted by domestic and industrial effluents of a highly industrialized region of São Paulo State, Brazil, by the comet assay in HTC cells

Abstract: The problems that most affect the quality of the waters of rivers and lakes are associated with the discharges performed in these environments, mainly industrial and domestic effluents inappropriately treated or untreated. The comet assay is a sensitive tool and is recommended for studies of environmental biomonitoring, which aim to determine the genotoxicity potential of water pollutants. This study aimed to assess the genotoxic potential of the Ribeirão Tatu waters, region of Limeira, São Paulo (SP), by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 40 publications
0
10
0
5
Order By: Relevance
“…According to Kabata-Pendias and Pendias (1992) and Manzano et al (2014), when the levels of metals are above the national regulation standards, they might become toxic to plants and other organisms. The high metal concentrations in the stream water found in our study might have resulted from the disposal of untreated effluent from the industrial district and agricultural areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Kabata-Pendias and Pendias (1992) and Manzano et al (2014), when the levels of metals are above the national regulation standards, they might become toxic to plants and other organisms. The high metal concentrations in the stream water found in our study might have resulted from the disposal of untreated effluent from the industrial district and agricultural areas.…”
Section: Discussionmentioning
confidence: 99%
“…The development of economic activities in the last five decades has caused an increase in the concentrations of metals in water resources, impacting the natural environment ( Matsumoto and Marin-Morales, 2005 ). According to Kabata-Pendias and Pendias (1992) and Manzano et al (2014) , when the levels of metals are above the national regulation standards, they might become toxic to plants and other organisms. The high metal concentrations in the stream water found in our study might have resulted from the disposal of untreated effluent from the industrial district and agricultural areas.…”
Section: Discussionmentioning
confidence: 99%
“…In our study Acid Black 210 showed no genotoxic effects on the HepG2 cells at concentrations between 0.5 and 5000 mg/mL by comet assay. Matsumoto et al (2003) showed the genotoxic potential of the water of a river receiving tannery effluents by the comet assay and Manzano et al (2015) showed the genotoxicity of waters impacted by domestic and industrial effluents. Both authors suggest that the genotoxicity could be associated with the metals discharged by the tanneries industries, especially chromium.…”
Section: Discussionmentioning
confidence: 99%
“…A limit of 80% of viable cells was considered to perform the comet assay (Manzano et al, 2015). The genotoxicity tests with insecticide imidacloprid, herbicide sulfentrazone and the mixture of them were performed separately in this study.…”
Section: Comet Assaymentioning
confidence: 99%